Factors Of National Health Insurance, Factors Of Health Service And Factors Of Social Security Administrator Influence On The Satisfaction Of Independent BPJS Class One At Kertha Usada General Hospital - Aditha Angga Pratama (Journal for Quality in Public Health, 2020)
Since 2004 Indonesia has campaigned for universal coverage as one of the improvements in health status. But until now there are still many Health insurance organizer (BPJS) participants who feel unsatisfied with the services they get, especially when Health insurance organizer participants are self-employed in class I inpatient services. The goal of this study is to identify the most dominant factor that can affect the satisfaction of Health insurance organizer participants' services in Kertha Usadha. The cross sectional survey research was conducted on 104 class 1 independent Health insurance organizer participants by simple random sampling. The selected Health insurance organizer participants were interviewed while in a state of hospitalization that was adjusted to the inclusion criteria of this study. The instrument used a structured questionnaire, with several related variables: characteristics, National Health Insurance factors, Health insurance organizer and health services. Variables were analyzed using Chi Square and then Logistic Regression with software. The results of this study found that 54.8% of B Health insurance organizer participants were satisfied with the services provided. While the results of multivariate analysis found that the factors influencing the satisfaction of Health insurance organizer participants were the National Health Insurance Factors that were good to moderate services (AOR: 1.2, 95% CI 0.8-1.43), good to less services (AOR: 3.4, 95% CI 1.5-7.53) and health service factors (AOR: 9.6, 95% CI 2.37-39.3). Health insurance organizer participant satisfaction is still low so it needs improvement in everything. So that later with increased satisfaction can improve the degree of public health